Angle-dependent magnetoresistance in organic metals - Blundell, S; Singleton, J (1996)
Recent experimental studies of the angle-dependent magnetoresistance in various organic metals have been remarkably successful in elucidating the nature of the low-temperature ground state and providing information about the Fermi surface shape which is hard or impossible to obtain using other techniques. We review various theoretical approaches to describe angle-dependent magnetoresistance and a number of important experimental results which have been obtained. ©Les Éditions de Physique 1996.